THE EXPERIMENTATION OF MIND MAP LEARNING AND PROBEM SOLVING MODEL TOWARD THE PREPAREDNESS OF FLOOD DISASTER AT IPS SUBJECTS OF THE SIXTH GRADE STUDENTS OF ELEMENTARY SCHOOL IN THE ACADEMIC YEAR OF 2012/2013 IN SUKOHARJO REGENCY. - Mustofa Mustofa; Chatarina Muryani; Suwarto W.A (GeoEco, 2016)
School has a direct influence to engraft preparedness to students in the knowledge and morality of facing flood disaster. The purposes of this study are to find (1) the difference between the flood disaster preparedness of students who are taught using a mind map learning model, problem solving, and direct instructional model, (2) the difference between the flood disaster preparedness of students who are taught using a mind map and problem solving model, (3) the difference between the flood disaster preparedness of students who are taught using a mind map anddirect instructional model, and (4) the difference between the flood disaster preparedness of students who are taught using a problem solving model anddirect instructional model. This study used a quasi-experimental method with 3 x 2 factorial design. The data analysis process used one-way Anova. From the inferential analysis, we found that: (1) There is a difference significant flood disaster preparedness between students who are taught using a mind map learning model, problem solving, and direct instructional model. (2) There is nothing a difference significant flood disaster preparedness between students who are taught using a mind map learning model and problem solving. (3) There is a difference significant flood disaster preparedness between students who are taught using a mind map learning model anddirect instructional model.(4) There is a difference significant flood disaster preparedness between students who are taught using a problem solving learning model anddirect instructional model.Keywords: mind map, problem solving, flood preparedness, initial ability